1993
DOI: 10.1002/1097-0142(19930301)71:5<1801::aid-cncr2820710515>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Mammography use and outcomes in a community the greater lansing area mammography study

Abstract: Background. Mammography is widely known to reduce morbidity and mortality from breast cancer, but a population‐based assessment of mammography use and follow‐up of mammography findings has not been reported previously. Methods. An observational, population‐based, follow‐up study was conducted of all women having mammograms in the Greater Lansing, Michigan, metropolitan area, between June 1987 and June 1988. A total of 17,811 Greater Lansing women participated. The adherence of women to mammography screening gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Locker et al (1989) calculated a sensitivity of 88% in a symptomatic population, but again follow-up information was not specified. In a largely asymptomatic population Sienko et al (1993) reported a sensitivity of 71% only and a specificity of 98%. In all studies mentioned above ultrasound was not used in the radiological work-up of breast disease.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Locker et al (1989) calculated a sensitivity of 88% in a symptomatic population, but again follow-up information was not specified. In a largely asymptomatic population Sienko et al (1993) reported a sensitivity of 71% only and a specificity of 98%. In all studies mentioned above ultrasound was not used in the radiological work-up of breast disease.…”
Section: Discussionmentioning
confidence: 96%
“…Comparison with other series is difficult as the positive predictive value of breast imaging depends on several other factors as well (Kopans, 1992). However, the integral use of mammography and ultrasonography will have helped us to obtain a positive predictive value that was substantially higher than in diagnostic studies in which ultrasound was not used (Wolfe et al, 1987;Robertson, 1993;Sienko et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inclusion criteria are often based on the degree, level, or seriousness of the abnormality 6, 13, 71–73, 83, 84, 89–91. For example, Sienko et al91 only included women with a mammographically detected abnormality necessitating a biopsy, whereas Haas et al90 included women with any type of abnormal mammogram results as well as women with clinical breast symptoms. In the area of cervical cancer, Palm et al83 included a wide range of abnormalities from mild dysplasia to invasive cancer, whereas Batal et al84 included only women with atypical squamous cells of undetermined significance or any dysplasia.…”
Section: Lessons Learnedmentioning
confidence: 99%